2021
DOI: 10.1111/ele.13770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple stressors on the dimensionality of ecological stability

Abstract: Ecological stability is a multidimensional construct. Investigating multiple stability dimensions is key to understand how ecosystems respond to disturbance. Here, we evaluated the single and combined effects of common agricultural stressors (insecticide, herbicide and nutrients) on four dimensions of stability (resistance, resilience, recovery and invariability) and on the overall dimensionality of stability (DS) using the results of a freshwater mesocosm experiment. Functional recovery and resilience to pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 49 publications
4
33
2
Order By: Relevance
“…Our study suggests that an increasing number of GCFs eliminate the positive effects of soil biodiversity on soil functions driven by soil microbes, e.g., nutrient cycling and soil microbial activity. Past research found that biodiversity can increase ecosystem functions when faced with a single or a number of GCFs 1 , 4 , 7 , 28 . Accordingly, biodiversity conservation, typically focused on aboveground organisms, is regarded as one of the best ways to sustain ecosystem functions 3 , 6 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that an increasing number of GCFs eliminate the positive effects of soil biodiversity on soil functions driven by soil microbes, e.g., nutrient cycling and soil microbial activity. Past research found that biodiversity can increase ecosystem functions when faced with a single or a number of GCFs 1 , 4 , 7 , 28 . Accordingly, biodiversity conservation, typically focused on aboveground organisms, is regarded as one of the best ways to sustain ecosystem functions 3 , 6 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Changing land use, pollutants and climate change are driving declines in biodiversity (Tickner et al., 2020) with associated effects on ecosystem and community stability (Fussmann et al., 2014). Ecosystem and community responses to environmental disturbance have recently been shown to be complex (Lemm et al., 2020; Polazzo & Rico, 2021) such that multiple components, or ‘dimensions’, of ecological stability should be measured (Donohue et al., 2013; Hillebrand et al., 2018; White et al., 2020; Yang et al., 2019). Dimensional components of stability include variability of biomass, abundance or percentage cover; resistance to change; rate of recovery following change; turnover of community composition; and rates of colonisations and extinctions (Clark et al., 2021; Donohue et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Though we test the applicability of our vulnerability framework in freshwater systems, OEV should also be a good candidate for other systems. However, its potential applicability across ecosystem realms needs to be investigated given that different ecological traits of organisms, as well as changing environmental contexts or disturbance types, have been shown to alter the effective dimensionality of ecological stability (Donohue et al, 2013(Donohue et al, , 2016Kéfi et al, 2019;Polazzo & Rico, 2021;Radchuk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that no single component itself reflects the integrated stability of the entire system (Donohue et al, 2013;Yang et al, 2019). Furthermore, the effective dimensionality of stability that emerges from the strength of these relationships can vary depending on the type of disturbance (Donohue et al, 2013;Polazzo & Rico, 2021;Radchuk et al, 2019), the organisms or ecological properties affected (Kéfi et al, 2019) and the spatial and temporal context in which disturbances occur (Clark et al, 2021;Güelzow et al, 2017;Levin, 1992). Thus, it is becoming increasingly clear that a multidimensional analytical approach to the study of stability is needed to reduce the risk of underestimating the overall impact of disturbances.…”
Section: Introductionmentioning
confidence: 99%